Predictors of antibody persistence to the 7-valent pneumococcal conjugate vaccine in healthy Fijian infants at 12 months of age - Lindholm, Daniel E.; Licciardi, Paul V.; Ratu, Felisita T.; Kim Mulholland, E.; Nguyen, Cattram D.; Russell, Fiona M. (Vaccine, 2020)
Little is known about the predictors of antibody persistence to pneumococcal conjugate vaccines (PCV) in the context of reduced dose schedules. In Fiji, an RCT investigated 0, 1, 2 and 3 dose schedules of 7-valent PCV administered at 6, 10 and 14 weeks of age in 364 healthy infants. This study was a post-hoc analysis of the predictors of poor antibody persistence at 12 months, prior to a booster, using univariable and multivariable analyses. The strongest predictors of poor antibody persistence as measured by serotype-specific immunoglobulin G (IgG) and opsonophagocytosis (OI) assays were being of Indigenous Fijian ethnicity (IgG: adjusted odds ratio (aOR) 3.43, p < 0.001; OI: aOR 1.96, p = 0.013) and receipt of fewer than 3 doses of PCV. These findings may help to identify which children may be at an increased risk of pneumococcal disease in the context of reduced dose primary series PCV schedules.